THE INFLUENCE OF LEARNING AWARENESS AND COGNITIVE ABILITY ON STUDENT ACHIEVEMENT - Epi Supriyani Siregar (Pedagogi: Jurnal Ilmiah Pendidikan, 2018)
This article examines the effect of mediating student learning awareness on cognitive abilities in improving academic achievement. This article discusses the role of teacher-student relationship variables and learning evaluation in encouraging the emergence of student learning awareness at the elementary school level. The data used are primary data, collected from 135 grade 5 and 6 teachers in 17 elementary schools in the Medan Polonia area, Medan City, Indonesia. Data analysis of Structural Equation Modeling (SEM) shows that there is a positive influence on the relationship and evaluation of learning on student achievement through learning awareness and cognitive abilities with a significant correlation (p < 0.05). This article's findings indicate that students' awareness of learning is a mediation that affects the improvement of cognitive abilities and academic achievement of students in the classroom.